First "Dead Sea Scroll" Found in Egypt Fifty Years Before Qumran Discoveries - Levy, Raphael (The Biblical archaeology review, 1982)
Some call it the first Dead Sea Scroll—but it was found in Cairo and not in a cave. It was recovered in 1897 in a Genizah, a synagogue repository for worn-out copies of sacred writings. The gifted scholar who had found it, Solomon Schechter, gave it with a hoard of other ancient Hebrew manuscripts […]